His-Ala-Phe-Lys peptide from Burkholderia arboris possesses antifungal activity - Zhu, Huajie; Xu, Cuihong; Chen, Yicun; Liang, Yan (Frontiers in Microbiology, 2022)
Burkholderia arboris, which belongs to the Burkholderia cepacia complex, has been shown to possess antifungal activity against several plant fungal pathogens; however, the antifungal compounds are yet to be identified. Here, we generated a Tn5 transposon mutation library of B. arboris and isolated mutants with reduced antifungal activity against the plant fungal pathogen Fusarium oxysporum. Among the mutants, the M464 mutant exhibited the weakest antifungal activity. In the M464 genome, the transposon was inserted into the cobA gene, encoding uroporphyrin-III methyltransferase. Deletion of the cobA gene also resulted in reduced antifungal activity, indicating that the cobA gene contributed to the antifungal activity of B. arboris. Furthermore, a comparison of the differential metabolites between wild type B. arboris and the M464 mutant showed a significant decrease in the level of tetrapeptide His-Ala-Phe-Lys (Hafk) compared with the wild type. Therefore, a Hafk peptide with D-amino acid residues was synthesized and its antifungal activity was evaluated. Notably, the Hafk peptide displayed significant antifungal activity against F. oxysporum and Botrytis cinerea, two plant pathogens that cause destructive fungal diseases. Overall, a novel antifungal compound (Hafk) that can be used for the biocontrol of fungal diseases in plants was identified in B. arboris.